Urban areas and global climate change - Holt, William G. (Bingley, U.K. : Emerald, 2012)
Examining urban environmental issues at the macro, municipal level down to the micro community and individual level, this volume features cities and metropolitan regions across the global north and south with case studies from the United States, Canada, Eastern and Western Europe to India, Central America, South America and Africa. Contributions on the global north examine: the role of governing processes in sustainable cities; local growth machines and their carbon consequences; tackling climate change adaptation through community participation; climate protection and the participation and engagement of citizens; the importance of networking; and assessing the success of the environmental justice within emissions trading schemes. Case studies on the global south look at such topics as: how resource-constraints shape climate adaptation; the emergence of low-carbon development; urban vulnerability and adaptation to the health impacts of air pollution and climate extremes; global environmental changes and impacts on fishing activities; environmental justice and the social construction of space in urban poor communities; and the inverse connection between gender and climate change.
ch. 1. Institutional and social capacities in lead cities in Europe and the United States : success factors for urban sustainability? / Corinna Altenburg -- ch. 2. Growth machines and carbon emissions : a county-level analysis of how U.S. place-making contributes to global climate change / Matthew Thomas Clement, James R. Elliott -- ch. 3. Tackling climate change adaptation at the local level through community participation / Geneviève Cloutier, Florent Joerin -- ch. 4. Climate protection and civil society : does effective local climate policy need the participation and engagement of citizens? : a comparison between the cities of Potsdam and Muenster / Mirjam Neebe, Fritz Reusswig -- ch. 5. Milan's answer to the climate change problem / Ilaria Beretta -- ch. 6. Win, lose, or draw? : assessing the success of the environmental justice movement in emissions trading schemes / Krystal Tribbett -- ch. 7. Climate adaptation in the face of resource constraints : lessons from a coastal South Asian mega-city / Madhu C. Dutta-Koehler -- ch. 8. Adapting to what? : climate change impacts on Indian megacities and the local Indian climate change discourse / Fritz Reusswig, Lutz Meyer-Ohlendorf -- ch. 9. Environmental state in transformation : the emergence of low-carbon development in urban China / Yifei Li -- ch. 10. Urban vulnerability and adaptation to the health impacts of air pollution and climate extremes in Latin American cities / Patricia Romero-Lankao ... [et al.] -- ch. 11. Cities in the flood : vulnerability and disaster risk management : evidence from Ibadan, Nigeria / Andrew Onwuemele -- ch. 12. Global environmental changes and impacts on fishing activities in the northern coast of São Paulo, Brazil / Sônia Regina da Cal Seixas ... [et al.] -- ch. 13. Climate change and the north coast of Jakarta : environmental justice and the social construction of space in urban poor communities / Rita Padawangi -- ch. 14. The gender dimensions of climatic impacts in urban areas : evidence and lessons from Kampala City, Uganda / Buyana Kareem.
Print version record
Keywords: Social Science -- Sociology -- General; Social Science -- General; Urban communities; Global warming; Urban ecology (Sociology); Climatic changes